Black currant phytoconstituents exert chemoprevention of diethylnitrosamine‐initiated hepatocarcinogenesis by suppression of the inflammatory response. Issue 4 (27th December 2011) - Bishayee, Anupam; Thoppil, Roslin J.; Mandal, Animesh; Darvesh, Altaf S.; Ohanyan, Vahagn; Meszaros, J. Gary; Háznagy‐Radnai, Erzsébet; Hohmann, Judit; Bhatia, Deepak
Abstract Black currant fruits containing high amounts of anthocyanins are known to possess potent antioxidant and anti‐inflammatory properties. We have previously reported that anthocyanin‐rich black currant skin extract (BCSE) inhibits diethylnitrosamine (DENA)‐initiated hepatocarcinogenesis in rats although the underlying mechanisms are not fully understood. Our present study investigates the anti‐inflammatory mechanisms of BCSE during DENA rat liver carcinogenesis. Dietary BCSE (100 or 500 mg/kg) treatment for 22 wk afforded a striking inhibition of DENA‐induced hepatic gamma‐glutamyl transpeptidase‐positive preneoplastic foci in a dose‐responsive fashion. There was a significant increase in hepatic expression of heat shock proteins (HSP70 and HSP90), cyclooxygenase‐2, and nuclear factor‐κB (NF‐κB) in DENA‐exposed rat livers. Dietary BCSE dose‐dependently abrogated all these elevated inflammatory markers. The possible cardiotoxicity of BCSE was assessed by monitoring cardiac functions using transthoracic echocardiography. BCSE‐mediated anti‐inflammatory effects during rat liver carcinogenesis have been achieved without any cardiotoxicity. Our results provide convincing evidence, for the very first time, that suppression of the inflammatory cascade through modulation of the NF‐κB signaling pathway could be implicated, at least in part, in the chemopreventive effects of black currant bioactive phytoconstituents against experimental hepatocarcinogenesis. These results coupled with an excellent safety profile of BCSE support the development of black currant phytochemicals for the chemoprevention of inflammation‐driven hepatocellular cancer. © 2011 Wiley Periodicals, Inc.